Code Mixing as a Communication Style Among South Jakarta Teenagers in Social Media - A Fitriani; Dewi Nandita Ramadhani (Palakka : Media and Islamic Communication, 2022)
ABSTRACTThe main concern of this study is to explore the trend of code mixing as a communication style in south Jakarta. This study is highly outline the why and how the use of code mixing among south Jakarta teenagers. To gain a powerful discussion, this study employs descriptive study which is the data were taken from research, journal, book, and other relevant sources. The conclusion reports that the appearance of code mixing among south Jakarta teenagers is influenced by 1) the use social media, 2) social environments, and 3) self-identity and recognition from community. Additionally, this trend can be positive for teenagers’ language and communication development but negative if this code mixing is potentially arise a misinterpretation.Keywords: Code Mixing, Communication Style, South Jakarta Teenagers